Affordance of Braille music as a mediational means: significance and limitations. Issue 2 (July 2014) - Park, Hyu-Yong; Kim, Mi-Jung
<x content-type="archive" xml:space="preserve">Abstract</x> Affordance refers to the properties or designs of a thing that offer the function of the thing. This paper discusses the affordance of Braille music in terms of three notions: mediational means, mastery and appropriation, and focuses on answering the following three questions: (i) How do musicians with visual impairments (MVI) perceive Braille music and what does it reveal about the characteristics and limitations of Braille music? (ii) What are the traits influencing the affordance of Braille music and how does it fit the needs of MVI? (iii) What are the conditions that make Braille music more affordable? To qualitatively investigate these topics, we interviewed nine music teachers and their seven students with visual impairment at a school for the blind in Korea. We found that learning and mastering Braille music is not an easy task, and that blind musicians tend to depend more on auditory input and memorisation. These findings suggest that the current level of development, diffusion and employment of Braille music is not satisfactory in Korea. In order to promote the affordance of Braille music, the adaptability, learnability/usability and availability of Braille music must be enhanced.